Imaging the Efficiency of Poly(3, 4‐ethylenedioxythiophene) Doped with Acid‐Functionalized Carbon Nanotube and Iridium Oxide Electrode Coatings for Microstimulation. Issue 7 (3rd May 2021) - Zheng, Xin S.; Yang, Qianru; Vazquez, Alberto L.; Tracy Cui, Xinyan
Abstract : Electrical microstimulation has shown promise in restoring neural deficits in humans. Electrodes coated with materials like the conducting polymer poly(3, 4‐ethylenedioxythiophene) doped with acid‐functionalized carbon nanotubes (PEDOT/CNTs, or PC) exhibit superior charge injection than traditional metals like platinum. However, the stimulation performance of PC remains to be fully characterized. Advanced imaging techniques and transgenic tools allow for real‐time observations of neural activity in vivo. Herein, microelectrodes coated with PC and iridium oxide (IrOx) (a commonly used high‐charge‐injection material) are implanted in GCaMP6s mice and electrical stimulation is applied while imaging neuronal calcium responses. Results show that PC‐coated electrodes stimulate more intense and broader GCaMP responses than IrOx. Two‐photon microscopy reveals that PC‐coated electrodes activate significantly more neuronal soma and neuropil than IrOx‐coated electrodes in constant‐voltage stimulation and significantly more neuronal soma in constant‐current stimulation. Furthermore, with the same injected charge, both materials activate more spatially confined neural elements with shorter pulses than longer pulses, providing a means to tune stimulation selectivity. Finite element analyses reveal that the PC coating creates a denser and nonuniform electric field, increasing the likelihood of activating nearby neural elements. PC coating can significantly improve energy efficiency for electrical stimulation applications. Abstract : The stimulation performance of two high‐charge‐injection materials poly(3, 4‐ethylenedioxythiophene) doped with acid‐functionalized carbon nanotube (PEDOT/CNT) and iridium oxide is examined. In vivo imaging results show that PEDOT/CNT is a more energy‐efficient material for cortical activation. In addition, for both materials, shorter stimulation pulses activate more spatially distinct neural elements than longer pulses, providing a means to tune stimulation selectivity.